Schizosaccharomyces pombe zfs1+ encoding a zinc-finger protein functions in the mating pheromone recognition pathway. - Kanoh, J (1995)
We isolated the Schizosaccharomyces pombe zfs1 gene as a multicopy suppressor of the sterility caused by overexpression of a double-stranded RNase. The deduced zfs1 gene product of 404 amino acids showed similarity to a mouse growth factor-inducible nuclear protein Nup475. Its C-terminal region carried two putative zinc-fingers, both of which should be intact for the protein to be functional as the suppressor. This protein appeared to localize in nuclei. Disruption of zfs1 was not lethal but conferred deficiency in mating and sporulation. Activation of transcription in response to the mating pheromone signaling was greatly reduced in the zfs1-disrupted cells. The mating deficiency of the zfs1-disruptant was suppressed partially by overexpression of either gpa1, ras1, byr1, or byr2, which are involved in the transmission of the pheromone signal. Disruption of zfs1 reduced both hypersensitivity of the ras1Val17 mutant to the mating pheromone and uncontrolled mating response caused by mutational activation of Gpa1, the G protein alpha subunit coupled to the mating pheromone receptors. However, overexpression of zfs1 could not bypass complete loss of function of either gpa1, ras1, byr1, or byr2. These observations indicate that the function of zfs1 is involved in the mating pheromone signaling pathway, and are consistent with its function being required to fully activate a factor in this pathway, either directly or indirectly.